RANCANG BANGUN ALAT KOLOM GELEMBUNG PANCARAN (JET BUBBLE COLUMN) UNTUK PENGURANGAN KADAR LOGAM BERAT LIMBAH CAIR INDUSTRI - Isran Asnawi; Hendi Lilih Wijayanto; Muhammad Alfian; Dewi Purnamasari (BRILIANT: Jurnal Riset dan Konseptual, 2026)
A jet bubble column is a reactor used in various process fields that functions to produce a strong liquid flow and expand the contact area between gases, liquids, and solids. However, research studies on the application of jet bubble columns for industrial wastewater treatment processes are still relatively limited. This study aims to modify the jet bubble column so that it can reduce the levels of heavy metals in industrial liquid waste. The tool is modified by adding granular adsorbents to the inside of the column which are held on a perforated plate holder. The tools and materials used include 5-inch PVC pipes, ½-inch PVC pipes, pipe fittings, pipe caps, hollow iron, DC pumps, valves, and brass nozzles. The jet bubble column tool has a fluid volume capacity of 5 L, a jet pump with a maximum pressure of 90 bar, a fluid flow rate of 7 L/minute, and a process time of 30 minutes. The test results show that the jet bubble column is able to reduce the levels of hexavalent heavy metals in industrial liquid waste by up to 83.67% with a contact time of 30 minutes. This shows better performance compared to the use of commonly used mechanical stirring.